Investigation of solar parabolic trough power plants with and without integrated TES (thermal energy storage) and FBS (fuel backup system) using thermic oil and solar salt. (August 2015) - Boukelia, T.E.; Mecibah, M.S.; Kumar, B.N.; Reddy, K.S.
Abstract: Thermodynamic, economic and environmental analyses of concentrating solar power plants assist in identifying an effective and viable configuration. In this paper, a 4E (energy-exergy-environmental-economic) comparative study of 8 different configurations of parabolic trough solar thermal power plants with two different working fluids (Therminol VP-1 -oil and molten solar salt), with and without integrated thermal energy storage or/and backup fuel system is presented. The results of the comparative study indicate relevant differences among the 8 configurations. The molten solar salt configuration with integrated thermal energy storage and fossil fuel backup system exhibits the highest overall energy efficiency (18.48%) compared to other configurations. Whereas, the highest overall exergy efficiency (21.77%), capacity factor (38.20%) and annual energy generation (114 GWh) are found for the oil based configuration with integrated thermal energy storage and fossil fuel backup system. The results indicate that the configurations based on molten salt are better in terms of environmental and economical parameters. The configurations with integrated thermal energy storage and fossil fuel backup system are found to be techno-economical, but on the other hand are less environment friendly. A detailed comparison of these plants after optimization must be performed before drawing a final conclusion about the best configuration to be adopted in parabolic trough solar thermal power plant. Highlights: 4E comparative study of 8 configurations of PTSTPP with two different fluids. Comparison of the configurations with and without integrated TES (thermal energy storage) and FBS (fuel backup system). The overall energy efficiency of the salt plant with TES and FBS is the highest. The overall exergy efficiency of the oil plant with TES and FBS is the highest. The salt plants are the best configurations in terms of environ–eco parameters.